A companion to modernist literature and culture - Bradshaw, David, 1955-; Dettmar, Kevin J. H., 1958- (Blackwell companions to literature and culture, 2006)
A Companion to Modernist Literature and Culture is an essential resource for students and teachers of modernism. The volume brings together entries on elements of modernist culture, contemporary intellectual and aesthetic movements, and all the genres of modernist writing and art.